AXIOM Approach for Modeling and Analysis of Complex Systems - Juha Panula-Ontto (Turku, 2022)
AXIOM is an approach for modeling and analysis of complex systems based on expert-sourced data. It proposes a systems modeling language and a computational process to extract information of higher analytical value from a model built using the language. AXIOM can be placed in the family of cross-impact analysis techniques, and it proposes solutions for several practical problems associated with systems modeling using the established cross-impact techniques. This paper presents the AXIOM modeling language primitives, outlines the computational process and shows how the evaluated AXIOM model can be used for analysis of the modeled system.
Futures of a Complex World: Proceedings of the Conference “Futures of a Complex World”, 12–13 June 2017, Turku, Finland